Влияние всесторонней изотермической ковки на микроструктуру и механические свойства высокоазотистой аустенитной стали - Ким, Анна Владимировна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The effect of multidirectional isothermal forging on the microstructure and mechanical properties of high-nitrogen austenitic steel has been studied. It is shown that during thermomechanical treatment the steel microstructure is fragmented with the formation of high- and low-angle boundaries. The studied thermomechanical treatment lead to an increase in yield strength in 2.5 times with a decrease in relative elongation.